2021
DOI: 10.1002/joa3.12516
|View full text |Cite
|
Sign up to set email alerts
|

Postimplantation pocket hematoma increases risk of cardiac implantable electronic device infection: A meta‐analysis

Abstract: Introduction  Several studies have shown an inconsistent relationship between postimplantation pocket hematoma and cardiac implantable electronic device (CIED) infection. In this study, we performed a systematic review and meta‐analysis to explore the effect of postimplantation hematoma and the risk of CIED infection. Methods  We searched the databases of MEDLINE and EMBASE from inception to March 2020. Included studies were cohort studies, case‐control studies, cross‐sectional studies, and randomized controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Several studies have identified risk factors for the development of CIED infections, for example, older age, end-stage kidney disease, and poorly controlled diabetes mellitus [ 9 ]. In addition, peri-implant complications, such as pocket hematoma requiring repeat intervention have also been associated with higher rates of device infection [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have identified risk factors for the development of CIED infections, for example, older age, end-stage kidney disease, and poorly controlled diabetes mellitus [ 9 ]. In addition, peri-implant complications, such as pocket hematoma requiring repeat intervention have also been associated with higher rates of device infection [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hematoma is among the most common complications, occurring in up to 3% of pacemaker cases and increasing the risk of other adverse effects, 2 including pacemaker infection. 3 The use of anticoagulation therapy further elevates the risk of hematoma following pacemaker or intracardiac defibrillator procedures. 1 , 4 Additionally, patients who experience hematoma complications have a slightly higher in-hospital mortality rate (1.3%) and incur significantly increased hospital costs of over $14,000 (US dollars).…”
Section: Discussionmentioning
confidence: 99%
“…Pocket hematoma that complicates CIEDs placement or invasive manipulation has been identified as a risk factor for infection [ 79 ]. Prevention of hematoma during the procedure is desirable: meticulous cautery of bleeding sites, application of topical thrombin, irrigation of the pocket, the use of monofilament suture for sub-cuticular layer, a pressure dressing applied for 12 to 24 h after skin closure may decrease the risk of hematoma formation [ 49 ].…”
Section: Prevention Of Cdriementioning
confidence: 99%